Investigation of Rock Failure Pattern in Creep by Digital Speckle Correlation Method - Yunliang Tan; Yanchun Yin; Tongbin Zhao (Advances in Materials Science and Engineering)
In order to study the mechanical characteristics from creep deformation to failure of rock, the tests of uniaxial compression and pushing steel-plate anchored in rock were performed, by using RLJW-2000 servo test synchronizing with Digital Speckle Correlation Method (DSCM). The investigations showed that for a uniaxial compressive specimen, when load arrived at 0.5σc, displacement clusters orderly formed, which was ahead of the macrocreep strain occurring in a slight jump mode when load arrived at 0.7σc. When the load level arrived at 0.8σc, displacement clusters gathered to be a narrow band. After that, the specimen abruptly fractured in a shear mode. In the creep pushing steel-plate test, when pushing force arrived at 25 kN, crack began to occur, the horizontal displacement field as well as shear strain field concentrated continuously along the interface between steel-plate and rock, and a new narrow concentrating band gathered in the upper layer. When pushing force arrived at 27.5 kN, another new narrow shear deformation band formed in the lower layer. Then, the steel-plate was pushed out quickly accompanying strong creep deformation.